1985
DOI: 10.1111/j.1432-1033.1985.tb08651.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of peptidyltransferase reactions by a soluble protein

Abstract: The requirements for peptide-bond synthesis and transesterification reactions of Escherichia coli 70s ribosomes, 50s native or reconstructed 50s subunits were examined using Met-tRNA as donor substrate and puromycin or a-hydroxypuromycin as acceptors.We report that the soluble protein EF-P, purified to apparent homogeneity, stimulates the synthesis of N-formylmethionylpuromycin or N-formylmethionylhydroxypuromycin by 70 S ribosomes or reassociated 30s and 50s subunits.In the presence of EF-P, 70s ribosomes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…However, several lines of evidence suggest that the ribosomal peptidyltransferase possesses catalytic residue(s) as well [l, 21. Of the known ribosomal activities, ester aminolysis and ester hydrolysis are most likely to be mediated by some form of catalytic mechanism. In this regard, we have recently reported that ribosomal protein L16 stimulates both the peptide-bond formation and transesterification activities inherent in peptidyltransferase [3]. This study confirmed and extended the findings of previous reconstitution experiments which showed that L16 belongs to a group of 50s subunit components designated as essential to restoring the peptidyltransferase activity of ribosomes [4].…”
Section: Reconstruction Of Peptidyltransferase Activity On 50 S and 7supporting
confidence: 79%
See 1 more Smart Citation
“…However, several lines of evidence suggest that the ribosomal peptidyltransferase possesses catalytic residue(s) as well [l, 21. Of the known ribosomal activities, ester aminolysis and ester hydrolysis are most likely to be mediated by some form of catalytic mechanism. In this regard, we have recently reported that ribosomal protein L16 stimulates both the peptide-bond formation and transesterification activities inherent in peptidyltransferase [3]. This study confirmed and extended the findings of previous reconstitution experiments which showed that L16 belongs to a group of 50s subunit components designated as essential to restoring the peptidyltransferase activity of ribosomes [4].…”
Section: Reconstruction Of Peptidyltransferase Activity On 50 S and 7supporting
confidence: 79%
“…AUG . f[35S]Met-tRNA complexes and added puromycin or hydroxypuromycin at concentrations of 4 pM and 8 pM, respectively [3].…”
Section: Pep T Idy Ltrans Ferase Assa Ysmentioning
confidence: 99%
“…This bifunctional role was studied by reconstituting L16 into core particles lacking L6, L11 and L16 [30]. Thus, L16 exhibits this role independently of the two stimulatory proteins L6 and L11.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence for a role in translation elongation comes from the ability of eIF5A to promote in vitro di-and tripeptide synthesis (12). To date, the effects of EF-P and its ␤-lysine modification on translation have largely been investigated using a puromycin reactivity assay, which does not accurately represent a physiologically relevant peptide synthesis reaction (2,13,14). We now show that EF-P functions in translation elongation, with activity dependent on ␤-lysylation, whereas the additional hydroxyl modification is dispensable.…”
mentioning
confidence: 99%